Improving the Communicative Competence in ESP of Students of Economics - Stefanova, Albena (Research Papers, 2021)
Academic courses in ESP are aimed at preparing students for successful functioning in a professional environment. Using the synergy between good traditional practices and the introduction of novel teaching techniques in the form of a new pedagogic model is one way of achieving greater course effectiveness and improved communicative competence in ESP of students of economics. Research is presented on the model revealing its benefits for optimised student performance.